(untitled) (Training and Practice : Journal of Educational Sciences, 2020)
The study investigates Hungarian CLIL learners’ (aged 13-14) beliefs on language learning and learning in the target language. Participants are all CLIL learners of a primary school located in a city (N=32). The base of the study is the application of mixed methods: a phonemic fluency test for the selections of learners and then structured interviews. In the first phase seven students with high scores in the phonemic fluency test were selected (N=7) of whom 3 participated in TELL (technology-enhanced language learning) classes. This paper presents the findings of the phonemic fluency test and the structured interviews. The processing of the structured interviews was done using qualitative content analysis.